Economic growth outlooks in sub-federal development strategies: prospects and constraints - Larisa Melnikova (European Regional Science Association (ERSA), 2014)
Inconsistencies in targeting and forecasting during the process of strategic planning in regions' subjects of Russian federation is atopic of the paper presented. It presents the results of analysis of regional strategies of long-term socio-economic development performed for federal subjects of Siberian and Far Eastern federal districts as well as for a group of largest federal subjects and macro-regions of Russia. The set of regional strategies may be considered as a unique sociological survey in which regions perform a role of interviewed subjects. A method of testing strategic documents of federal subjects in terms of their consistency and availability of resources is presented. The method involves a) analysis of targeting in sub-federal strategies; b) aggregation of isolated forecasts of subjects of the same federal district; c) a comparison of the aggregate of independent sub-federal strategic forecasts with the complex long-term spatial forecast of socio-economic development of Russian economy. The authors of regional forecasts have an advantage of local knowledge, of the economic situation, but they are not able to account all resource constraints that arise when intersectoral and interregional relations between production and exchange of goods in the economy (or within a larger macro-region) are analyzed. Such possibility is provided by the use of a national and spatial input-output models unified in the model complex. It provides forecasts in the cut of 8 federal districts (including Tyumen) and 40 economic activities. This result confirms the assumption of a lack of validity of regional administrations' investment plans. According to the forecasts based on OIIM, in the years 2006?2020, the Russian economy is unable to provide investments stated in regional forecasts. The results of a comparative analysis of the resource security of regional strategies and a verification of independent regional GDP growth forecasts by regions of Siberia, Far east and other macro-regions showed a potential of interregional competition for labor and investment resources. It is shown that a regional strategy is often used as a means of competition with other regions for federal resources. The basic problems are formulated that should be solved in order to make regional strategies actually important element of improving the system of regional governance and the document of public consensus between the government, business, and the population in respect of key issues of regional development.
Keywords: D78; R11; R15; R58; 330; Consistency of sub-federal forecasts; long-term development strategies; regional growth